Prevalence of vitamin D deficiency in children with sickle cell anemia: a systematic review - Isabela G. Bristotte; Natália V. S. Daniel; Luciana Pietro (Brazilian Journal of Health and Biomedical Sciences, 2023)
Introduction: Sickle cell anemia is a highly prevalent genetic disease in the Brazilian population, mainly present in black ethnic groups from slave migration, as well as from the miscegenation process. It is a disease of clinical expression of the homozygosity of the hemoglobin S gene, which may be a genetic and/or hereditary disease, caused by the replacement of the normal residue of glutamic acid by the amino acid valine in the sixth position of the polypeptide chains of the beta-globin protein, generating biochemical alteration in the hemoglobin S molecules, which polymerize inside the erythrocyte and transform into a sickle cell. The possible lack of vitamin D may be linked to disease processes, as well as to the individual's painful crises. Objectives: To analyze whether or not there was a prevalence of vitamin D deficiency in children with sickle cell anemia, through a systematic review. Methodology: A systematic review was carried out by searching for original articles in the scientific databases: Pubmed, Science Direct, Lilacs and Scielo in the languages: English and Portuguese. Results: It was found that out of 10 articles, 8 showed the prevalence of vitamin D deficiency (< 20 ng/ml) in children with sickle cell anemia. Conclusion: The prevalence of vitamin D deficiency was high in patients with the disease, so that its supplementation may serve as a means of assisting in the treatment to improve the condition and prevent deficiency. However, more targeted studies with this association and/or intervention are needed to have more concrete results.